2017
DOI: 10.3892/ol.2017.6025
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-96-5p inhibits autophagy and apoptosis and enhances the proliferation, migration and invasiveness of human breast cancer cells

Abstract: Abstract. MicroRNAs (miRNA/miR) are short non-coding RNAs that function in the endogenous regulation of genes. miRNAs serve important roles in cellular events such as apoptosis, cell proliferation, migration, invasion, autophagy and the cell cycle. They also control the genesis and progression of tumors. Autophagy is a self-digestive process that occurs as a response to stress, and serves two opposite roles in tumor promotion or inhibition that may result in resistance to therapy. A number of studies have reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 76 publications
2
46
0
Order By: Relevance
“…Six miRNAs were identified in the present study, and the results showed that the levels of miR-96-5p, miR-222-5p, and miR-652-5p were overexpressed, while miR-125-5p, miR-145-3p, and miR-379-3p levels were down-regulated in GAC sample. Several studies have demonstrated that miR-96-5p is overexpressed in various cancers, including colorectal cancer [13], pancreatic carcinoma [14], prostate cancer [15], hepatocellular carcinoma [16], and breast cancer [17], and it is oncogene that promotes cell proliferation. It has been reported that miR-652-5p is associated with non-small cell lung cancer [18], esophageal adenocarcinoma [19], and breast cancer [20], while the mechanism of miR-652-5p was not elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…Six miRNAs were identified in the present study, and the results showed that the levels of miR-96-5p, miR-222-5p, and miR-652-5p were overexpressed, while miR-125-5p, miR-145-3p, and miR-379-3p levels were down-regulated in GAC sample. Several studies have demonstrated that miR-96-5p is overexpressed in various cancers, including colorectal cancer [13], pancreatic carcinoma [14], prostate cancer [15], hepatocellular carcinoma [16], and breast cancer [17], and it is oncogene that promotes cell proliferation. It has been reported that miR-652-5p is associated with non-small cell lung cancer [18], esophageal adenocarcinoma [19], and breast cancer [20], while the mechanism of miR-652-5p was not elaborated.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of that, miRNA-96 silencing induces an increase in γ-globin [32,33]. In addition, overexpression of miRNA-96-5p inhibits autophagy and apoptosis in human breast cancer cells [34]. Thus, although our results are referred to RBCs, this evidence could indicate that miRNA-96 decrease might be a sign of ongoing RBC autophagy and apoptosis.…”
Section: Discussionmentioning
confidence: 44%
“…In consistent with these studies, the present study shows that miR-192-5p could target FOXO1, and its dysregulation was involved in hyperglycemia and insulin resistance. Indeed, it has been shown that the expression of FOXO1 and acetylated-FOXO1 is regulated by miR-96-5p in human breast cancer cell [13]. These studies suggest that the expression of FOXO1 is regulated by different miRNAs.…”
Section: Discussionmentioning
confidence: 92%
“…It has been documented that FOXO1 is regulated by miRNA. For example, it has been reported that miR-96-5p inhibited autophagy via downregulation of the expression of FOXO1 and acetylated-FOXO1 in human breast cancer cell [13]. However, the relationship between circHIPK3 and FOXO1/diabetes remains largely unknown.…”
mentioning
confidence: 99%